The influence of language and culture on a South African corporate - Nirvana Bechan; Ronelda Visser (Communicare)
This study investigates whether the different home languages of the employees in a South African corporate have an influence on their perception of the organisational structure and processes. The study was conducted in the context of the ABSA financial institution in the Western Cape. The authors conducted a series of interviews with management-level employees who speak Afrikaans, English and Xhosa as home languages, in an attempt to ascertain the extent of the influence of individual cultures on perceptions and actions in corporate society. Specific attention was given to how these individuals perceived meetings, decision-making processes and conflict. These interviews were transcribed verbatim and studied by means of narrative analysis using a specialised software package to provide better insight into the roles that language and culture play in a South African organisation. Based on the narratives provided by the respondents in this study, the authors concluded that individual culture plays a significant role in the perceptions of organisational structures such as conflict management, interaction during meetings, decision-making and the acceptance of authority. South Africa is now celebrating more than ten years of democracy following the country’s first democratic election in 1994. In the past decade, corporate South Africa has seen an unprecedented cultural diversity in its workforce. The dynamics of local organisations have changed to incorporate the various cultural representations. In an attempt to explore the multicultural phenomenon that exists in the workplace, the authors conducted a study among the supervisory and managerial staff of a prominent South African financialinstitution, ABSA, in the hope of providing better insight into the roles language and culture play in a South African organisation. Such an understanding could not only establish a more effective organisational culture, but also ultimately help South African business to deal with cultural diversity and conflict in the workplace in a more creative way. This article describes a qualitative research project utilising narrative analysis to investigate how employees’ home language influences their perception of corporate culture.